Deleuzian feminism: Becoming woman in new Turkey cinema - Avci, Ikbal Bozkurt (IGI Global, 2022)
Minority refers to a distinct deviation from something of which standards and norms are clear. In this direction, "becoming-woman, " which is revealed by Deleuze as the first becoming type is quite impressive for feminist theory. Women can enter into becoming-woman by disturbing the dichotomic order with their line of flight instead of acting according to the identities imposed on them. This study is based upon the concept of becoming-woman in the context of Deleuzian feminism tries to approach the issue of "becoming-woman" in the new Turkey cinema based on the film Zephyr (2011) by Belma Bas. The film is evaluated according to the three basic elements of minor cinema. © 2022, IGI Global.